ANALISIS IDENTIFIKASI MASALAH UTAMA KOPERASI DI KABUPATEN BANYUASIN DALAM MEWUJUDKAN KESEJAHTERAAN ANGGOTA - Mubarok, Nurul; Jannah, Sinta Ardhillatul; Laksanawati, Septi (I-Economics, 2018)
Abstract Banyuasin Regency, especially the Air Kumbang sub-district, has cooperatives in every village, however, existing cooperatives face various problems. identification of initial problems that often occur are as follows: The level of participation of members in the process of developing their organizational activities is still low. The quality and quantity of HR, market access, institutional access, access to finance and information and the use of appropriate technology are still minimal. The low understanding of philosophy, history and cooperative ideology is part of a weakness that has an impact on different perceptions or perspectives that are increasingly distant from their character. Other problems some cooperatives / actors in cooperative management activities tend to be easily intervened. They are only oriented to one side, namely business in order to gain income without consciously making a loss at the expense of their identity. The research method used is qualitative research using Triangulation data analysis techniques. Triangulation is essentially a multi-method approach conducted by researchers when collecting and analyzing data. The basic idea is that the phenomenon under study can be well understood so that high levels of truth can be obtained if approached from various points of view. Photographing a single phenomenon from different points of view will enable reliable levels of truth to be obtained. Therefore, triangulation is an attempt to check the truth of data or information obtained by researchers from various different perspectives by reducing as much bias as possible during data collection and analysis. Based on the results of the analysis found The main problems faced by Cooperatives in Banyuasin district, Early years planning that is not mature, Distrust members to cooperative management, Difficulties in the management of each block / limited knowledge, Limited human resources, Prices of rising goods cause losses, Lack of understanding the duties and authorities of both supervisors and administrators, lack of understanding of the latest cooperative regulations, not understanding members about the main goals and objectives of cooperative formation, lack of management understanding of the objectives and main objectives of cooperatives is to prosper their members, more visible in the field cooperative managers who are paid by members, business development that does not exist, or business managers do not play well. The lack of business development from cooperatives leads to not maximal profits, Lack of knowledge and skills in managing cooperatives (due to self-taught learning) causing financial planning in the beginning not in accordance with implementation, one of which does not take into account inflation, the manager's opening costs and financial reporting. cause members to lack trust in management, financial statement deficits that often occur from year to year, one of the causes is not estimating inflation or rising prices of goods and rising transportation costs during the initial planning of work programs designed. And the steps to improve the welfare of cooperative members are the development of new businesses, holding training and development, and training in the preparation of RAB and financial reports for administrators Abstrak Kabupaten Banyuasin khususnya kecamatan Air Kumbang memiliki Koperasi di setiap desa akan tetapi, koperasi yang telah ada menghadapi berbagai permasalahan. Identifikasi permasalahan awal yang sering terjadi adalah sebagai berikut: Tingkat partisipasi anggota dalam proses pengembangan kegiatan organisasinya yang masih rendah. Kualitas dan kuantitas SDM, akses pasar, akses kelembagaan, akses pembiayaan dan informasi serta penggunaan teknologi tepat guna yang masih minim.Masalah lainnya beberapa pelaku/ perangkat koperasi dalam kegiatan pengelolaan koperasi cenderung mudah terintervensi. Mereka hanya berorientasi pada satu sisi yakni usaha dalam rangka meraih pendapatan dengan tanpa sadar melakukan kerugian dengan mengorbankan jati dirinya. Metode penelitian yang dilakukan adalah penelitian kualitatif dengan menggunakan tekhnik analisis data Triangulasi. Triangulasi pada hakikatnya merupakan pendekatan multi metode yang dilakukan peneliti pada saat mengumpulkan dan menganalisis data. Ide dasarnya adalah bahwa fenomena yang diteliti dapat dipahami dengan baik sehingga diperoleh kebenaran tingkat tinggi jika didekati dari berbagai sudut pandang. Berdasarkan hasil analisis ditemukan Masalah utama yang dihadapi oleh Koperasi di kabupaten Banyuasin, Perencanaan awal tahun yang tidak matang, Ketidakpercayaan anggota kepada pengurus koperasi, Kesulitan manajemen tiap-tiap blok/ keterbatasan pengetahuan, Keterbatasan SDM,Harga-harga barang naik menyebabkan kerugian, Kurangnya pemahaman tugas dan wewenang masing-masing baik pengawas maupun pengurus, Kurangnya pemahaman mengenai peraturan-peraturan koperasi terbaru,Tidak mengertinya anggota mengenai sasaran dan tujuan utama dari pembentukan koperasi, Kurangnya pemahaman pengurus akan sasaran dan tujuan utama koperasi adalah untuk mensejahterahkan anggotanya, dilapangan lebih terlihat bahwa pengurus koperasi yang digaji oleh para anggota, Pengembangan bisnis yang tidak ada, atau manajer bisnis nya tidak berperan dengan baik. Kurangnya pengembangan bisnis dari koperasi menyebabkan keuntungan yang tidak maksimal, Kurangnya pengetahuan dan keterampilan dalam mengelola koperasi (dikarenakan belajar otodidak) menyebabkan perencanaan keuangan diawal tidak sesuai dengan pelaksanaan, salah satunya tidak memperhitungkan inflasi, Ketidakterbukaan pengurus akan pengeluaran biaya-biaya dan pembuatan laporan keuangan, menyebabkan anggota kurang percaya terhadap kepengurusan, Defisit laporan keuangan yang sering terjadi dari tahun ke tahun, salah satu penyebabnya adalah tidak memperkirakan inflasi atau kenaikan harga-harga barang dan kenaikan biaya transportasi pada saat perencanaan awal program-program kerja yang dirancang. Dan langkah-langkah Peningkatan kesejahteraan anggota koperasi adalah Pengembangan bisnis baru, Mengadakan pelatihan dan pengembangan, dan Pelatihan penyusunan RAB dan Laporan Keuangan bagi pengurus Kata Kunci : Koperasi, Identifikasi masalah, Kesejahteraan.